Food availability according to food security- insecurity among Mexican households. - Reyna Guadalupe Valencia-Valero; Luis Ortiz-Hernández (Instituto Nacional de Salud Pública, 2014)
Objective. To know the differences in food availability according to food insecurity level among the Mexican households. Materials and methods. We analyzed the database of the National Survey of Household's Incomes and Expenditures (n=27 445 households). Households were classified according to the Latin American and Caribbean Inventory of Food Security. The availability of each food group was estimated as grams per day per equivalent adult. Results. 50.0% of Mexican households experienced some degree of food insecurity. Among households with food insecurity there was high availability of corn, wheat, egg, and sugars; but there was low availability of fresh fruits and vegetables, lean meat, poultry, seafood, milk, cheeses, and sweetened beverages. Conclusion. Although in households with food insecurity there is lower availability of most food groups (both with high nutrient density and with high energy density); they have higher availability of cheap foods, which in some cases are only source of energy but do not provide nutrients.